(untitled) (Journal of Pharmaceutical Negative Results, 2022)
1,3-oxazepine-4,7-dione derivatives [O1-O4] was synthesized with the [2-5] cycloaddition reaction of malic anhydride and phthalic anhydride with azoimine [S1 – S2]. Synthesis of azo compound [A1 – A2] from 4-aminobenzene sulphonic acid by coupling diazonium salt to 4- hydroxybenzaldehyde phenoxide anion and 4-octylbenzaldehyde phenoxide anion. The aldehyde groups in the azoaldehyde derivatives [A1 – A2] were condensed with 4-nitro aniline in the presence of glacial acetic acid as a catalyst in absolute ethanol to give azoimine derivative [S1 – S2]. The resulting azoimine derivative [S1 – S2] were then introduced into [2-5] the cycloaddition reaction with malic, phthalic of anhydride compounds. The molecules were characterized via FTIR and 1HNMR spectra. Estimate the activity of synthetic compounds as antibacterial.